IIR Filter Order and Cut-off Frequency Influences on EMG Signal Smoothing - Zahari, Taha; Deboucha, Abdelhakim; Ahamed, Nizam Uddin; Anwar, P. P. A. Majeed; Wong, Yashim (Biomedical India, 2015)
Infinite Impulse Response (IIR) filters are the fundamental signal processing technique to analyze the surface Electromyography (sEMG). These filters are defined by their particular orders (e.g. first-, second- or third-order) and the frequency they passed through. Although, EMG signals from human skeletal muscles are important to realize the muscle features, but there is no consistency found in the literature regarding the influence of different orders of the filter and cutoff frequency when processing and filtering EMG signal during lower limb (Biceps Femoris) muscle contraction. It is therefore important to know the response of muscle EMG signal after changing the order of filters and cut-off frequencies. Thus, this paper addresses the behavior of the signal patterns after varying the filter order and cut-off frequency of the filter. To record the EMG signal, one healthy male participated in this study after obtaining his informed consent and the electrodes were placed on the lower limb Biceps Femoris muscle during sit-to-stand task at a normal speed. During the signal processing, the cut-off frequency of the filter was fixed with the variation of the order of the filter. Later, the order of the filter was fixed while the cut-off frequency was varied. Finally, the results show that varying the order of filter (while frequency fixed) does not distort the EMG signal significantly, whereas varying the frequency changes the shape of the signal considerably